Effects of Tung Oil-Based Polyols on the Thermal Stability, Flame Retardancy, and Mechanical Properties of Rigid Polyurethane Foam - Zhou, Wei (Polymers (Basel), 2018)
A phosphorus-containing tung oil-based polyol (PTOP) and a silicon-containing tung oil-based polyol (PTOSi) were each efficiently prepared by attaching 9,10-dihydro-9-oxa-10-phosphaphenanthrene (DOPO) and dihydroxydiphenylsilane (DPSD) directly, respectively, to the epoxidized monoglyceride of tung oil (EGTO) through a ring-opening reaction. The two new polyols were used in the formation of rigid polyurethane foam (RPUF), which displayed great thermal stability and excellent flame retardancy performance. The limiting oxygen index (LOI) value of RPUF containing 80 wt % PTOP and 80 wt % PTOSi was 24.0% and 23.4%, respectively. Fourier transfer infrared (FTIR), Nuclear Magnetic Resonance (NMR) and thermogravimetric (TG) analysis revealed that DOPO and DPSD are linked to EGTO by a covalent bond. Interestingly, PTOP and PTOSi had opposite effects on T(g) and the compressive strength of RPUF, where, with the appropriate loading, the compressive strengths were 0.82 MPa and 0.25 MPa, respectively. At a higher loading of PTOP and PTOSi, the thermal conductivity of RPUF increased while the RPUF density decreased. The scanning electron microscope (SEM) micrographs showed that the size and closed areas of the RPUF cells were regular. SEM micrographs of the char after combustion showed that the char layer was compact and dense. The enhanced flame retardancy of RPUF resulted from the barrier effect of the char layer, which was covered with incombustible substance.